1980
DOI: 10.1159/000179304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LH-RH Treatment on Hypothalamo-Pituitary-Gonadal Axis and Leydig Cell infrastructure in Cryptorchid Boys

Abstract: 62 cryptorchid boys aged 2–6 years were selected at random either for surgical or for hormonal LH-RH treatment. As all biopsies from boys operated show typical histological and ultrastructural signs of cryptorchidism, it can be concluded that only true cryptorchid patients are included in our study. LH-RH treatment was successful in 16 (55%) of 31 boys. Median 30-min response values to LH-RH test of LH were initially normal in all boys. Those treated successfully remain normal after treatment whereas unsuccess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…prior to surgery (Canavese, 2009). In a study by Hadziselimovic et al, in which the effect of LHRH nasal spray on testicular descent was analysed, neither a stimulatory effect nor an inhibitory effect on the number of germ cells was seen (Hadziselimovic, 1980). This in contrast to Cortes et al, who found a negative effect on germ cells in 1-3-year-old boys with cryptorchidism after gonadotropin releasing hormone (GnRH) (Cortes, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…prior to surgery (Canavese, 2009). In a study by Hadziselimovic et al, in which the effect of LHRH nasal spray on testicular descent was analysed, neither a stimulatory effect nor an inhibitory effect on the number of germ cells was seen (Hadziselimovic, 1980). This in contrast to Cortes et al, who found a negative effect on germ cells in 1-3-year-old boys with cryptorchidism after gonadotropin releasing hormone (GnRH) (Cortes, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…The success rate of GnRH therapy, which has been carried out since 1975 by the nasal spray method, varies between 30 and 50% [9,11,12]. It emerges from our randomised study [12] that after completion of therapy LH values 30 min after intravenous GnRH are lower in patients without descent than in boys in whom GnRH therapy induced a descent.…”
Section: Discussionmentioning
confidence: 84%
“…In boys where the treatment was not successful, the spermatogonia count remained un changed compared with those treated unsuc cessfully with only GnRH or surgical meth ods [12]. EM findings confirmed that the Leydig cells were stimulated ( fig.…”
Section: Histology'mentioning
confidence: 79%
“…Some investigators surmised that after LHRH stimulation LH and FSH cooperate to potentiate the local action of testosterone or to increase local testoster one secretion and thereby testicular descent due to dif ferentiation of the epididymis and ductus deferens [46,47], However, wc found no evidence for lasting stimula tion of the hypothalamic-pituitary-testicular axis. There were identical, slight changes in plasma gonadotropin as well as testosterone levels after LHRH treatment and placebo.…”
Section: Lh-releasing Hormonementioning
confidence: 99%